Research on size effect of gas explosion in the roadway. (June 2021) - Tan, Bo; Liu, Yanling; Liu, Huilin; Wang, Haiyan; Li, Tianze
Highlights: The law of gas explosion propagation is affected by size effect. The larger size of the roadway will strengthen the positive feedback mechanism. The smaller the roadway size is, the greater damage of the pressure wave generated. The roadway with larger size consumes methane at a faster rate. The local accumulation of CO is more obvious in the roadways with larger. Abstract: Mine gas explosion accident is one of the most harmful coal mine disasters. Usually, it will cause a lot of property losses and casualties, which seriously restricts the healthy development of the coal mining industry. In this paper, Fluent software is used to simulate gas explosions in straight roadways of different sizes and it is concluded that Fluent software can be used to accurately simulate gas explosion conditions after comparing with the experimental data. Besides, the results of the study show that the propagation law of gas explosion in the straight roadway of different sizes is affected by the size effect. The roadway with a larger size will enhance the positive feedback mechanism of the combustion reaction rate and flame propagation speed. The flame propagation speed is faster and the local accumulation of CO is more obvious in the roadway with a larger size. The smaller the size of the roadway, the greater the pressure peak it generates. The research results can provide theoretical support and an experimental basis for the prevention and control of gas explosion accidents.